On the Compactness of the Commutator of the Parabolic Marcinkiewicz Integral with Variable Kernel. (12th November 2014) - Chen, Yanping; Zhu, Kai; Ding, Yong
Abstract : The authors prove that the commutator of the parabolic Marcinkiewicz integralg Ω with variable kernel is a compact operator onL p ( R n ) ( 1 < p < ∞ ) if and only ifb ∈ C M O ( R n, ρ ) . The result is substantial improvement and extension of some known results.